"Now it is all over…I am practically No-Body": Indigenous Veterans of Canada and Australia and the Great War for Civilization. Issue 1 (2nd January 2019) - Winegard, Timothy C.
ABSTRACT: At the onset of war in 1914, no imperialist European state, save for France, regarded its colonial Indigenous populations as a source of military manpower for a European war. Contemporary science, social biases and public opinion accepted that certain identifiable ethnic groups lacked the intelligence and integrity to fight modern war. It was also accepted that since these groups were the subjects of vast European empires, prudence warned against allowing them to fight in a European war, thus forfeiting white racial supremacy. By late 1915, however, with escalating casualties and an increasing demand for manpower, Britain specifically requested the military inclusion of Indigenous populations from its five Dominions including Canada and Australia. The elevated participation of Indigenous peoples from Canada and Australia during the First World War was the potential pivotal catalyst to accelerate their attainment of equal rights. For the first time in history, they had been summoned, in unprecedented numbers, to fight and labour on foreign fields alongside men from across the empire, and other Allied nations. For all nations, the sacrifice of the First World War was measured in blood and the staggering tally of the butcher's bill. This was no different for the Indigenous peoples of Canada and Australia. Men and women from the far reaches of empire fought alongside their European counterparts and shared equally in the burdens of the war both on the battlefields and the Home Fronts. They voluntarily aided the British Empire in its time of need and viewed the war as a potential pivotal catalyst to accelerate their attainment of equal rights. This did not happen. In peace, their services were no longer needed, or wanted. After the war, prejudicial governmental policy in Canada and Australia continued to dominate political discourse and Indigenous veterans returned to their pre-war status as subjugated peoples, banished to the shadows and the fringes of conventional society. Most were denied veterans benefits, including the assistances of the various postwar soldier settlement programmes.